Upregulation of the PatAB Transporter Confers Fluoroquinolone Resistance to Streptococcus pseudopneumoniae - Alvarado, María; Martín-Galiano, Antonio J.; Ferrándiz, María J.; Zaballos, Ángel; de la Campa, Adela G. (Frontiers in Microbiology, 2017)
We characterized the mechanism of fluoroquinolone-resistance in two isolates of Streptococcus pseudopneumoniae having fluoroquinolone-efflux as unique mechanism of resistance. Whole genome sequencing and genetic transformation experiments were performed together with phenotypic determinations of the efflux mechanism. The PatAB pump was identified as responsible for efflux of ciprofloxacin (MIC of 4 ug/ml), ethidium bromide (MICs of 8-16 ug/ml) and acriflavine (MICs of 4-8 ug/ml) in both isolates. These MICs were at least 8-fold lower in the presence of the efflux inhibitor reserpine. Complete genome sequencing indicated that the sequence located between the promoter of the patAB operon and the initiation codon of patA, which putatively forms an RNA stem-loop structure, may be responsible for the efflux phenotype. RT-qPCR determinations performed on RNAs of cultures treated or not treated with subinhibitory ciprofloxacin concentrations were performed. While no significant changes were observed in wild-type Streptococcus pneumoniae R6 strain, increases in transcription were detected in the ciprofloxacin-efflux transformants obtained with DNA from efflux-positive isolates, in the ranges of 1.4 to 3.4-fold (patA) and 2.1 to 2.9-fold (patB). Ciprofloxacin-induction was related with a lower predicted free energy for the stem-loop structure in the RNA of S. pseudopneumoniae isolates (-13.81 and -8.58) than for R6 (-15.32 kcal/mol), which may ease transcription. The presence of these regulatory variations in commensal S. pseudopneumoniae isolates, and the possibility of its transfer to Streptococcus pneumoniae by genetic transformation, could increase fluoroquinolone resistance in this important pathogen.